1987
DOI: 10.3354/meps035001
|View full text |Cite
|
Sign up to set email alerts
|

Metals in liver and kidney tissues of autumn-migrating dunlin Calidrisalpina and curlew sandpiper Calidris ferruginea staging at the Baltic Sea

Abstract: Concentrations of 10 metals (Ca, Cd, CO, Cu, Fe, Mg, Mn, Pb, V and Zn) were determined in Liver and kidney tissues of dunlin Calidris alpha (n = 70) and curlew sandpiper Calidris ferruginea (n = 28). Element associabons are reported. Significant linear correlations were found between renal and hepatic concentrations of cadmiun~, copper, magnesium, and manganese. Copper showed an agerelated concentration decrease, whereas cadmium concentration increased with age. Mean biological half-life of renal cadmium in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…The essential elements iron, zinc, and copper measured in livers of shorebirds in this study were within the ranges normally found in other shorebirds (Blomqvist et al 1987;Lee et al 1987;Hui 1998;Hui et al 2001;) and are probably maintained there by normal homeostatic mechanisms for shorebird species.…”
Section: Heavy Metal Concentrationsmentioning
confidence: 84%
“…The essential elements iron, zinc, and copper measured in livers of shorebirds in this study were within the ranges normally found in other shorebirds (Blomqvist et al 1987;Lee et al 1987;Hui 1998;Hui et al 2001;) and are probably maintained there by normal homeostatic mechanisms for shorebird species.…”
Section: Heavy Metal Concentrationsmentioning
confidence: 84%
“…Third, in waders such as the red knot and the curlew sandpiper, first year birds do not reproduce, but remain in the winter quarters throughout the first summer (Elliott et al 1976;van Dijk et al 1990;Summers et al 1995), while in geese first year birds migrate to the arctic breeding areas, although without reproducing (Ebbinge 1989). Finally, the red knot and the curlew sandpiper considered in the present study have a rather limited breeding range on and near the Taimyr peninsula (Blomqvist et al 1987;Tomkovich and Soloviev 1996), and so may be expected to respond to the same breeding conditions, in contrast to other tundra-nesting bird species, such as the white-fronted goose Anser a. albifrons, sanderling Calidris alba, and ruddy turnstone Arenaria interpres, which have more extended breeding ranges (Cramp andSimmons 1977, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Iron concentrations in livers of the Western Reef heron and Siberian gull were significantly different, which differs from Hui (1998) in southern California who reported no differences between black-billed plovers (Pluvialis squatarola) and willets (Catoptrophorus semipalmatus). Kim et al (2009b) quantified mean iron concentrations of 467 lg/g in liver from Terek sandpiper, and, similarly, Blomqvist et al (1987) obtained mean concentrations of 463 lg/g from dunlin (Calidris alpina) liver samples. Both were considerably greater than in birds from Hara Biosphere Reserve.…”
Section: Heavy-metal Concentrationsmentioning
confidence: 99%